Blood oxygen saturation is lower in persons with pre-diabetes and screen-detected diabetes compared with non-diabetic individuals: A population-based study of the Lolland-Falster Health Study cohort - Laursen, Jens Christian; Jepsen, Randi; Bruun-Rasmussen, Neda Esmailzadeh; Frimodt-Møller, Marie; Jørgensen, Marit Eika; Rossing, Peter; Hansen, Christian Stevns (Frontiers in Epidemiology, 2022)
Aims: Low blood oxygen saturation is associated with increased mortality and persons with diabetes have sub-clinical hypoxemia. We aimed to confirm the presence of sub-clinical hypoxemia in prediabetes, screen-detected diabetes and known diabetes. Methods: Prediabetes was defined as hemoglobin A1C (HbA1C) ≥ 42 mmol/mol and < 48 mmol/mol; known diabetes as history or treatment of diabetes; screen-detected diabetes as no history or treatment of diabetes and HbA1C ≥ 48 mmol/mol. Blood oxygen saturation was measured with pulse oximetry. Urine albumin-to creatinine ratio (UACR) was measured on a single spot urine. Results: The study included 829 adults (≥ 18 years) with diabetes (713 (86%) with known diabetes; 116 (14%) with screen-detected diabetes) and 12,747 without diabetes (11,981 (94%) healthy controls; 766 (6%) with prediabetes). Mean (95% CI) blood oxygen saturation was 96.3% (96.3% to 96.4%) in diabetes which was lower than in non-diabetes (97.3% (97.2% to 97.3%)) after adjustment for age, gender, and smoking (p < 0.001), but significance was lost after adjustment for BMI (p = 0.25). Sub-groups with prediabetes and screen-detected diabetes had lower blood oxygen saturations than healthy controls (p-values < 0.01). Lower blood oxygen saturation was associated with higher UACR. Conclusions: Persons with prediabetes and screen-detected diabetes have sub-clinical hypoxemia, which is associated with albuminuria.